Antropologi Al-Qur’an: Integrasi Keilmuan Kisah-Kisah Al-Qur’an dan Pokok-Pokok Antropologi Koentjaraningrat - Imam Subchi (ILMU USHULUDDIN, 2019)
Koentjaraningrat is an Indonesian anthropologist who has many ideas. An interesting Koentjaraningrat idea in relation to the Quran is 7 (seven) elements of culture as an ethnographic principle. This idea opens new horizons related to the Anthropology of the Quran. The subjects in the study of Al-Quran Anthropology have focused on the linguistic verses of the Quran without trying to reveal other anthropological elements such as those contained in the stories of the Quran. This study will integrate 7 elements of culture in anthropology with the stories in the Quran, such as language, science and technology, economics and livelihoods, social systems and social organizations, arts, and religion. The results of this study are thay stories in the Quran in accordance with these 7 elements of culture. Al-Quran, thus contains historical and anthropological stories that are in accordance with the development of science, especially anthropology.